Odometry of computer mice - Chan, Daniel Bai Yang. (2010)
Sensors are vital components in an Autonomous Guided Vehicle (AGV) system. It enables the AGV to know its pose. This project intends to study the feasibility of making use computer mice to retrofit it to a robot’s pose sensor.